AllergoOncology – the impact of allergy in oncology: EAACI position paper. Issue 6 (23rd January 2017) - Jensen‐Jarolim, E.; Bax, H. J.; Bianchini, R.; Capron, M.; Corrigan, C.; Castells, M.; Dombrowicz, D.; Daniels‐Wells, T. R.; Fazekas, J.; Fiebiger, E.; Gatault, S.; Gould, H. J.; et al.
Abstract: Th2 immunity and allergic immune surveillance play critical roles in host responses to pathogens, parasites and allergens. Numerous studies have reported significant links between Th2 responses and cancer, including insights into the functions of IgE antibodies and associated effector cells in both antitumour immune surveillance and therapy. The interdisciplinary field of AllergoOncology was given Task Force status by the European Academy of Allergy and Clinical Immunology in 2014. Affiliated expert groups focus on the interface between allergic responses and cancer, applied to immune surveillance, immunomodulation and the functions of IgE‐mediated immune responses against cancer, to derive novel insights into more effective treatments. Coincident with rapid expansion in clinical application of cancer immunotherapies, here we review the current state‐of‐the‐art and future translational opportunities, as well as challenges in this relatively new field. Recent developments include improved understanding of Th2 antibodies, intratumoral innate allergy effector cells and mediators, IgE‐mediated tumour antigen cross‐presentation by dendritic cells, as well as immunotherapeutic strategies such as vaccines and recombinant antibodies, and finally, the management of allergy in daily clinical oncology. Shedding light on the crosstalk between allergic response and cancer is paving the way for new avenues of treatment. Abstract :